Patriarcavirus, feminist dystopias and COVID-19: Reflections on the phenomenon of gender pandemics - Machado-Jiménez, Almudena (Feminismo/s, 2021)
This essay examines contemporary feminist dystopias to study the phenomenon of gender pandemics. Gender pandemic narrative allegorises possible aftermaths of patriarcavirus, unleashing many natural disasters that force global biopolitics to hinder gender equality. The main objective of this essay is to explain how gender pandemics are appropriated in patriarchal utopian discourses as a pretext to control female empowerment, diagnosing women as diseased organisms that risk the state’s well-being. Moreover, the novels explore the interdependence between biology and sociality, portraying the acute vulnerability of female bodies during and after the pandemic conflicts, inasmuch as patriarchal power arranges a hierarchical value system of living that reinforces gender discrimination. Particularly, the COVID-19 emergency is analysed as a gender pandemic: the exacerbated machismo and the growing distress in the female population prove that women are afflicted with a suffocating patriarcavirus, which has critically gagged them in the first year of the pandemic.
https://feminismos.ua.es/article/view/19380
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; arts; corps; covid-19; discipline; droits des femmes*; genre; patriarcat; précarité; périodes historiques; ressource en ligne; santé; systèmes d'oppressions; thématiques; violences; études littéraires

Symptômes - Ocelot, Catherine (Éditions Pow Pow, 2021)
"Comme des plantes qui s’enlacent dans une serre, les récits de Symptômes s’entrecroisent et s’imbriquent les uns dans les autres pour exposer les liens qui nous unissent, mais aussi la façon dont les relations, qu’elles soient toxiques ou saines, se répercutent sur notre corps et notre esprit. Et si des fils invisibles nous reliaient pour toujours à ceux qui ont joué un rôle dans notre vie?"–Rabat de la couverture.
Section: 276 pages : illustrations en couleur ; 21 cm
Keywords: amériques; arts; bande-dessinée; canada; care; corps; cours; discipline; lit3495; premier cycle; québec; ressource en ligne; roman graphique; régions géographiques; santé; thématiques; études littéraires